The Comparative Study of Urban Sprawl in Cities of North Khorasan Province (Case Study: Esfarayen and Bojnord) - Moslem Nori; Rostam Saberifar; Esmaeil Aliakbari (تحقیقات کاربردی علوم جغرافیایی)
The change in the way cities operate and benefit from ICTs, etc., has led to population dispersal, activity, and housing. This trend, along with the devastating social and environmental impacts, has had quite visible and measurable economic consequences. A comparative study would be very helpful to avoid the implications of measuring the occurrence of this process and the impact of national and local factors on it. Therefore, the purpose of the present study is to compare the dispersal trend of the two cities of Esfarain and Bojnourd. In this regard, the present study is applied in terms of purpose and analytical-comparative in terms of research method. Required data were collected from documentary library studies and Heldern, Shannon entropy and Gini coefficients were used to analyze the data. The results showed that according to Helderen's model, 84% of physical growth in Esfarain between 1345 and 1345 was related to population growth and about 16% to horizontal and spherical growth. For Bojnourd, this was also about 88% of the population growth and about 12% of the horizontal and spiral growth, which is slightly different from that of Esfarain. The Shannon entropy model also shows the sparse growth of physical expansion in the two cities of Esfarain and Bojnourd. The Gini coefficient calculated for Esfarain city is 0.096 and for Bojnourd city is 0.054 which indicates that population growth (Espalier) of Esfarain city is 0.015% more than Bojnourd city. Since the continuation of such conditions has numerous environmental, social and economic consequences for the residents of the cities concerned, it is advisable to strategically research, control and manage the physical development of the city and utilize the interpersonal development policy.